PENURUNAN KONSENTRASI KROMIUM (Cr) DALAM LIMBAH CAIR ELECTROPLATING DENGAN PENGGUNAAN KOAGULAN DAN ADSORBEN - Ratih Artanti; Sigit Yuli Jatmiko (Jurnal Ecolab, 2011)
The research was conducted at the Integrated Laboratory, Indonesian Agricultural Environment Research Institute (IAERI), Jakenan, Pati, Central Java. Treatment for electroplating wastewater samples taken from Talang Subdi strict, Tegal District, Central Java was managed as chemically that was through the coagulation and flocculation processes. The purpose of this study was to test the effectiveness of coagulant and adsorbent materials in reducing the concentration of electroplating wastewater Cr. Experiments used a factorial design in randomized completely block design and three replications. The first factor was the coagulant materials, namely: control, alum (Al2(SO4.xH2O)), sodium bisulphate (NaHSO4), and resin anion, while the second factor was the adsorbent materials, namely: control, activated carbon, and zeolite. The results showed that all coagulants (sodium bisulphate, alum, and resin anion), adsorbent materials (activated carbon and zeolite) and a combination of both significantly decreased the concentration of electroplating wastewater Cr more than 50%. Resin anion and its combination with activated carbon as well as with zeolite were very effective in decreasing the concentration of electroplating wastewater Cr (97-98%). Coagulant and adsorbent combination, resin anion+activated carbon and resin anion+zeolit, had double function that decreased of both Cr consentration and TDS (Total Dissolved Solid) of the concentration of electroplating wastewater.